Linc00668 Promotes Invasion and Stem Cell-Like Properties of Breast Cancer Cells by Interaction With SND1 - Qian, Wenchang; Zhu, Yong; Wu, Mingming; Guo, Qianying; Wu, Zhengsheng; Lobie, Peter E.; Zhu, Tao (Frontiers in Oncology, 2020)
Long non-coding RNAs (lncRNAs) are reported to be involved in breast cancer progression. Herein, we observed that the expression of Linc00668 was increased in breast cancer compared to normal tissue. The patients with high Linc00668 expression exhibited an association with a higher metastatic risk. We demonstrated that forced expression of Linc00668 enhanced, whereas depletion of Linc00668 diminished invasion and self-renewal of breast cancer cells as well as resistance to doxorubicin (Dox). Further mechanistic studies revealed that Linc00668 associated with staphylococcal nuclease domain-containing 1 (SND1) and regulated the expression of downstream genes. Linc00668 depletion led to reduced expression of the downstream target of SND1 and further attenuated the self-renewal capacity of breast cancer cells. Our observations suggest that Linc00668 promotes metastasis, and chemotherapeutic resistance in breast cancer by interacting with SND1. Therefore, Linc00668 may serve as a potential therapeutic modulator in breast cancer treatment.